Adverse drug reaction profiles of commonly used platinum compounds in cancer chemotherapy - Swathi, B.; Bhavika, D.; Begum, Naseem (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The aim of the present study was to monitor and analyze the pattern of occurrence of adverse drug reactions (ADRs) to commonly used platinum compounds in MNJ Cancer Hospital, Hyderabad. Methods: Cancer patients, who received platinum compounds as chemotherapy regimen, were monitored for adverse reactions. Cancer patients belonging to either gender and of all ages, who were receiving platinum compounds under any standard regimen, were included for the study. Cases that were unlikely, conditional or unaccessible under World Health Organization (WHO)-Uppsala Monitoring Centre causality criteria were excluded from the study. The ADRs were recorded in Central Drugs Standard Control Organization forms. Causality was assessed by the WHO Causality Assessment Scale and Naranjo’s Algorithm. Preventability and severity of ADRs were assessed by modified Schumock and Thornton scale, modified Hartwig and Siegel scale, respectively. Results: Among 100 patients, 78 developed ADRs to platinum compounds. The reactions observed were vomiting, diarrhea, abnormal renal function tests, myelosuppression, anemia, thrombocytopenia, alopecia, and constipation. The WHO Causality Assessment Scale indicated 64.6% “possible” and 35.4% “probably,” but no “certain” reactions. Naranjo’s Algorithm showed 59.4% “possible” 40.6% “probable” reactions. 48% reactions were “definitely preventable” 16% were “probably preventable” and 36% were “not preventable.” Modified Hartwig and Siegel Scale of severity assessment showed that 12% reactions were “mild” 69% were “moderate” and 19% were severe. Conclusion: Platinum compounds have high potential for adverse effects. There is a need to improve the management of adverse effects. This study also emphasizes the need to improve pharmacovigilance awareness among physicians in order to improve the pharmacovigilance in India.